2017
DOI: 10.4314/ijah.v6i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Benefits derived from recreation and sport leisure that motivate participation

Abstract: Using the constraints-effects mitigation model, this study explored the benefits of recreation and sport leisure activities that motivate women's participation. While there are numerous studies that have investigated factors that motivate women's leisure participation and leisure constraints in Europe and the United States, there are less empirical studies conducted in sub-Saharan Africa. A lack of comparable studies limits our understanding of leisure participation in Africa, but more importantly mandates fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In the current study, a total of thirty-three of the thirty-four parents identified social benefits as a factor for their rugby participation decision. Of academic interest, however, is that while rates of concussion can be, and have been repeatedly, shown to be highly elevated for rugby participation, no research shows that rugby offers unique mental, social, or physical health benefits compared to other team sports [ 63 ]. Further, contact forms of rugby offer no unique well-being benefits over non-contact forms of rugby [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, a total of thirty-three of the thirty-four parents identified social benefits as a factor for their rugby participation decision. Of academic interest, however, is that while rates of concussion can be, and have been repeatedly, shown to be highly elevated for rugby participation, no research shows that rugby offers unique mental, social, or physical health benefits compared to other team sports [ 63 ]. Further, contact forms of rugby offer no unique well-being benefits over non-contact forms of rugby [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, activities considered as leisure differ with geographic location and cultural settings. Women's burden has been exacerbated by culturally underpinned expectations, such as women's submission [10]. These societal and institutionalized norms are often used to model women's behavior around men and how they need to appear.…”
Section: Introductionmentioning
confidence: 99%